2006
DOI: 10.1590/s0104-11692006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical occupational risks identified by nurses in a hospital environment

Abstract: RIESGOS OCUPACIONALES QUÍMICOS IDENTIFICADOS POR ENFERMEROS QUE TRABAJAN EN AMBIENTE HOSPITALARIO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
5
0
5
Order By: Relevance
“…It has also been suggested that ‘nurses need further information on occupational chemical risks such as antineoplastic substances and antibiotics, which they might receive in undergraduate or continuous education courses, because nurses have contact with chemical substances in the course of their duties’ (Xelegati et al. , p. 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that ‘nurses need further information on occupational chemical risks such as antineoplastic substances and antibiotics, which they might receive in undergraduate or continuous education courses, because nurses have contact with chemical substances in the course of their duties’ (Xelegati et al. , p. 1).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 33.7% of working students reported exposure to chemical hazards at work. In a study of nurses at the emergency care unit of a university hospital in Brazil, participants confirmed they came in contact with different chemical compounds in their work environment and they indicated that occupational exposure to these substances can cause health problems (21).…”
Section: Discussionmentioning
confidence: 99%
“…23 Porém, estudos realizados identificaram que para os profissionais da saúde expostos às substâncias químicas, o glutaraldeído é uma das substâncias mais prejudiciais à saúde. 24,25,26 O glutaraldeído é considerado perigoso, porém não cancerígeno. 27 No meio ambiente, a substância em questão é considerada tóxica para organismos aquáticos.…”
Section: Ntroduçãounclassified